Organic compound with multiple heteroatoms and organic electroluminescent device comprising same

By using organic compounds with multiple heteroatoms in organic electroluminescent devices, and introducing electron-absorbing substituents and nitrogen-containing heteroaryl groups with strong electronegative properties, the problem of reducing carrier utilization caused by hole diffusion is solved, and the effect of improving carrier utilization and device luminescence efficiency is achieved.

CN119874776APending Publication Date: 2025-04-25SHIJIAZHUANG CHENGZHI YONGHUA DISPLAY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510054584.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In existing organic electroluminescent devices, the diffusion of holes to the N-type charge-generating material leads to a decrease in carrier utilization, and how to weaken this diffusion to improve carrier utilization becomes key.

Method used

Using organic compounds with multiple heteroatoms, the electron-absorbing substituents with strong electronegative electronegativity such as triazine, pyridine, phosphine oxygen structures is introduced to increase the electron transport capability and hole blocking capability of the material. Specifically, it includes connecting two phosphine oxygen structures on ring structures such as benzene ring or triazine, and introducing nitrogen-containing heteroaryl groups on either side of phenanthroline to enhance the HOMO energy level and carrier injection efficiency of the material.

Benefits of technology

The electron transport capability and carrier injection efficiency of the material are significantly improved, the diffusion of holes to the N-type charge generation material is weakened, and the carrier utilization rate and device luminescence efficiency are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874776A_ABST
    Figure CN119874776A_ABST
Patent Text Reader

Abstract

The invention discloses an organic compound with a plurality of heteroatoms and an organic electroluminescent device comprising the same. The structural general formula of the organic compound is shown as a formula I. According to the invention, by using a plurality of electron-withdrawing substituents with strong electronegativity such as triazine, pyridine and phosphine oxide structures, the ESP absolute value of the material is obviously increased, the electron transport capability of the material and the coordination capability of the material with a metal doped material are improved, and especially when two phosphorus oxide structures are simultaneously connected under the same benzene ring, triazine and other ring structures, the ESP absolute value of the material is obviously increased. And the increase of the absolute value of the ESP is facilitated. Besides, the invention also finds that nitrogen-containing heteroaryl is introduced to any side of phenanthroline, namely Ar1 and / or Ar2 positions, the HOMO energy level of the material can be deepened, so that the potential barrier of hole transport is increased, diffusion of holes to an N-type charge generation material is weakened, the utilization rate of current carriers is increased, and the luminous efficiency of the device is improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of OLED, and specifically comprises an organic compound having multiple heteroatoms and an organic electroluminescent device comprising the same. Background Art

[0002] After more than two decades of rapid development, organic electroluminescent devices (OLEDs), as a new generation of flat panel display devices, have shown obvious advantages and have gradually been recognized by people. They are ultra-thin, colorful, short response time, wide color gamut, high contrast, and can provide highly saturated red, green, and blue colors. They have been widely used in flat panel displays, flexible displays, solid-state lighting, and automotive displays.

[0003] In current organic electroluminescent devices, multiple light-emitting units are connected by charge generation layer materials. The use of multi-layer series technology can significantly improve the luminescence life of the device. Among them, the stability of the charge generation layer has a great influence on the device life and driving voltage. Early studies have found that by changing the n-type charge generation material (nCGL), the driving voltage of the device can be significantly reduced, but the luminescence efficiency of the device is often not significantly improved. In early studies, no better solution was provided for improving device efficiency through nCGL materials. The improvement in efficiency requires adjusting the overall device material combination to achieve.

[0004] The study found that after holes and electrons are generated in the charge generation layer, they will pass through the p-type / n-type charge generation layer and further migrate to the adjacent light-emitting unit. The holes generated at the interface of the p-type / n-type charge generation layer have a certain probability of migrating to the n-type charge generation layer, which will lead to a decrease in carrier utilization. How to weaken the diffusion of such holes to the N-type charge generation material to improve the carrier utilization becomes the key. Summary of the invention

[0005] In view of the above problems existing in the prior art, the present invention provides an organic compound having multiple heteroatoms and an organic electroluminescent device comprising the same.

[0006] To achieve the above objectives, the technical solutions adopted by the present invention include:

[0007] The first aspect of the present invention provides an organic compound having multiple heteroatoms, characterized in that the general structural formula of the organic compound is as shown in Formula I:

[0008]

[0009] in,

[0010] Ar1 represents a substituted or unsubstituted aryl group having C6-C60 carbon atoms, a substituted or unsubstituted condensed ring aryl group having C6-C60 carbon atoms, or a substituted or unsubstituted heteroaryl group having C5-C60 carbon atoms;

[0011] Ar2 represents one of hydrogen, a substituted or unsubstituted aryl group having carbon atoms of C6-C60, and a substituted or unsubstituted heteroaryl group having carbon atoms of C5-C60;

[0012] Ar3 and Ar4 represent groups represented by formula II;

[0013]

[0014] L1 represents a single bond, a substituted or unsubstituted aryl group having carbon atoms of C6-C60, or a substituted or unsubstituted condensed ring aryl group having carbon atoms of C6-C60;

[0015] L2, L3, and L4 each independently represent a single bond or a phenylene group.

[0016] Furthermore, at least one of Ar1 and Ar2 represents a nitrogen-containing heteroaryl group having a carbon number of C5-C60.

[0017] Furthermore, Ar1 represents one of phenyl, triazine, naphthyl, anthracenyl, fluorenyl, methyl-substituted fluorenyl, benzimidazole, quinoxaline, quinazoline, and pyridine.

[0018] Furthermore, Ar2 represents one of hydrogen, phenyl, naphthyl, pyridine and pyrimidine.

[0019] Furthermore, the L1 represents a single bond or a phenylene group.

[0020] Furthermore, L3 and L4 represent a single bond.

[0021] Furthermore, the organic compound is selected from one of the following general structures:

[0022]

[0023]

[0024] Further, the organic compound is selected from Formula I-1, Formula I-2, Formula I-3, Formula I-7, Formula I-8 or Formula I-12, and Ar2 represents pyridine or pyrimidine.

[0025] Further, the organic compound is selected from Formula I-4, Formula I-5, Formula I-6, Formula I-9, Formula I-10, Formula I-11 or Formula I-13, and Ar2 represents one of hydrogen, phenyl, naphthyl, pyridine and pyrimidine.

[0026] Furthermore, the organic compound is selected from one of the following structures:

[0027]

[0028]

[0029]

[0030]

[0031] The second aspect of the present invention provides an organic electroluminescent device, comprising an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer, which are sequentially arranged on a substrate; wherein the charge generation region includes one or more organic compounds as described above.

[0032] Furthermore, the charge generation region includes an n-type charge generation layer and a p-type charge generation layer, wherein the n-type charge generation layer includes one or more organic compounds as described above.

[0033] Beneficial effects of the present invention:

[0034] The present invention significantly increases the ESP absolute value of the material by using a plurality of electron-withdrawing substituents with strong electronegativity such as triazine, pyridine, phosphine oxygen structure, etc., improves the electron transmission ability of the material and the ability of coordination with metal-doped materials, especially when two phosphorus oxygen structures are simultaneously connected to the same benzene ring, triazine and other ring structures, it is more beneficial to increase the ESP absolute value. In addition, when such materials are used for n-type charge generation materials, their coordination with the doped metal is more firm, thereby enhancing the injection efficiency of its carriers, and further improving the device efficiency. The present invention also finds that the compound introduces a nitrogen-containing heteroaryl group on either side of phenanthroline, which can deepen the HOMO energy level of the material, thereby increasing the potential barrier of hole transmission, weakening the diffusion of holes to the N-type charge generation material, improving the carrier utilization rate, and improving the device luminous efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic structural diagram of the organic electroluminescent device of the present invention. DETAILED DESCRIPTION

[0036] In order to more clearly understand the content of the present invention, it will be described in detail with reference to the drawings and embodiments.

[0037] The organic compound of the present invention is suitable for use in light-emitting elements, display panels and electronic devices, and is particularly suitable for use in organic electroluminescent devices. The electronic device of the present invention is a device comprising a layer of at least one organic compound, and the device may also comprise an inorganic material or a layer formed entirely of an inorganic material. The electronic device is preferably an organic electroluminescent device (OLED). The schematic structural diagram of an exemplary organic electroluminescent device is shown in FIG. Figure 1 shown.

[0038] Experimental Section

[0039] In order to understand the content of the present invention more clearly, the luminescent characteristics of the organic compound, the preparation method of the organic compound and the device will be explained in detail in conjunction with the examples. Various chemical reactions can be applied to the synthetic method of the compound of one embodiment of the present invention. However, it should be noted that the synthetic method of the compound of one embodiment of the present invention is not limited to the synthetic method described below. Unless otherwise indicated, the subsequent synthesis is carried out in anhydrous solvent under a protective gas atmosphere. Solvents and reagents can be purchased from conventional reagent suppliers.

[0040] Synthesis Example 1

[0041]

[0042] Compound Sub-1 (8.2 g, 20.0 mmol), Sub-2 (8.9 g, 48.0 mmol), palladium acetate (0.44 g, 2.0 mmol), potassium phosphate (12.8 g, 60 mmol) were added to 100 ml of toluene and refluxed for 4 hours under nitrogen protection. After the reaction was completed, the reaction system was cooled to room temperature, and the solvent was removed by rotary evaporation. The crude product was redissolved in 100 ml of dichloromethane, and 30 ml of 30% hydrogen peroxide was added and stirred at room temperature for 3 hours. After the reaction was completed, the liquid was separated, the organic phase was dried over anhydrous sodium sulfate, and then dried by rotary evaporation. The product Sub-3 (7.9 g, 14.1 mmol) was purified by column chromatography, MS (m / z) (M+): 557.0, yield 71%.

[0043] Sub-3 (7.9 g, 14.1 mmol), biboric acid pinacol ester (3.8 g, 15 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to 300 ml DMF solution, and then tetrakistriphenylphosphine palladium (1.2 g, 1 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110 ° C, stirred for 8 hours, and then 300 ml of water and 300 ml of toluene were added after cooling to room temperature and separated, and the organic phase was dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by petroleum ether: dichloromethane = 1: 1 (v / v) column. Finally, the product B1 (6.8 g, 11.3 mmol) was obtained, MS (m / z) (M+): 605.2, yield: 80%.

[0044]

[0045] A1 (2.6 g, 10 mmol), B1 (6.8 g, 10 mmol) and potassium carbonate (2.1 g, 15 mmol) were added to a mixed solution of 300 ml toluene: water = 4: 1 (v / v), and then tetrakis triphenylphosphine palladium (1.2 g, 1 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110 ° C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried with anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by petroleum ether: dichloromethane = 10: 1 (v / v) column. Finally, the product C1 was obtained: 5.5 g, yield: 76%, MS (m / z) (M+): 733.2.

[0046] Synthesis Example 2

[0047]

[0048] Compound Sub-4 (8.2 g, 20.0 mmol), Sub-5 (16.2 g, 40.0 mmol) and potassium carbonate (8.2 g, 60 mmol) were added to 300 ml of DMF solution, and then tetrakistriphenylphosphine palladium (2.4 g, 2 mmol) was introduced under nitrogen protection, and stirred at 80° C. for 4 hours. After the reaction was completed, the reaction system was cooled to room temperature, and the solvent was removed by rotary evaporation, and the product Sub-6 (10.6 g, 15 mmol) was purified by column chromatography, MS (m / z) (M+): 710.2, yield 75%.

[0049] Sub-6 (10.6 g, 15 mmol), biboric acid pinacol ester (4.0 g, 16 mmol) and potassium carbonate (4.1 g, 30 mmol) were added to 300 ml DMF solution, and then tetrakistriphenylphosphine palladium (1.2 g, 1 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110 ° C, stirred for 8 hours, and then 300 ml of water and 300 ml of toluene were added after cooling to room temperature and separated, and the organic phase was dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by petroleum ether: dichloromethane = 1:1 (v / v) column. Finally, the product B2 (8.8 g, 11.7 mmol) was obtained, MS (m / z) (M+): 758.3, yield: 78%.

[0050]

[0051] A2 (2.6 g, 10 mmol), B2 (7.6 g, 10 mmol) and potassium carbonate (2.1 g, 15 mmol) were added to a mixed solution of 300 ml toluene: water = 4: 1 (v / v), and then tetrakis triphenylphosphine palladium (1.2 g, 1 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110 ° C, refluxed and maintained for 8 hours, cooled to room temperature, quenched with water and separated, the organic phase was dried with anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by petroleum ether: dichloromethane = 10: 1 (v / v) column. Finally, the product C2 was obtained: 4.7 g, yield: 59%, MS (m / z) (M+): 810.2.

[0052] Synthesis Example 3

[0053]

[0054] Using the same method as in Synthesis Example 2, A3 (2.6 g, 10 mmol) and B3 (7.3 g, 10 mmol) were used to replace A2 and B2, and finally product C3 was obtained: 4.2 g, yield: 54%, MS (m / z) (M+): 783.2.

[0055] Synthesis Example 4

[0056]

[0057] Using the same method as in Synthesis Example 2, A4 (3.4 g, 10 mmol) and B4 (6 g, 10 mmol) were used to replace A2 and B2, and finally product C4 was obtained: 3.9 g, yield: 53%, MS (m / z) (M+): 733.2.

[0058] Synthesis Example 5

[0059]

[0060] Under nitrogen atmosphere, Sub5-1 (50 g, 135 mmol), nickel chloride hexahydrate (2.38 g, 10 mmol), 2,2'-bipyridine (3.12 g, 20 mmol), zinc powder (13.1 g, 200 mmol) and diphenylphosphine oxide (54.6 g, 270 mmol) were suspended in water (1000 mL) and stirred at 70 ° C for 16 hours. Dichloromethane (500 mL) was poured into the reaction mixture, filtered, and the filter cake was washed with dichloromethane. After the filtrate was separated, the aqueous layer was extracted with dichloromethane (200 mL*2), and the combined organic layer was dried over magnesium sulfate and concentrated under reduced pressure.

[0061] The crude product was separated and purified using a petroleum ether: dichloromethane = 2:1 (v / v) column to finally obtain the product Sub5-3 (50.5 g, 82.3 mmol), MS (m / z) (M+): 613.1, yield: 61%.

[0062] Sub5-3 (50.5 g, 82.3 mmol), biboric acid pinacol ester (22.8 g, 90 mmol) and potassium carbonate (24.6 g, 180 mmol) were added to 1500 ml DMF solution, and then tetrakistriphenylphosphine palladium (7.2 g, 6 mmol) was introduced under nitrogen protection, and then the reaction system was heated to 110 ° C, stirred for 8 hours, and then 1000 ml of water and 1000 ml of toluene were added to separate the liquids after cooling to room temperature. The organic phase was dried over anhydrous sodium sulfate, the solvent was removed by rotation, and the crude product was separated and purified by petroleum ether: dichloromethane = 1:1 (v / v) column. Finally, the product B5 (6.8 g, 45.3 mmol) was obtained, MS (m / z) (M+): 605.2, yield: 55%.

[0063] Synthesis Example 6

[0064]

[0065] Using the same method as in Synthesis Example 2, A6 (3.4 g, 10 mmol) and B6 (8.4 g, 10 mmol) were used to replace A2 and B2, and finally product C6 was obtained: 5.5 g, yield: 57%, MS (m / z) (M+): 964.3.

[0066] Synthesis Example 7

[0067]

[0068] Using the same method as in Synthesis Example 2, A7 (3.4 g, 10 mmol) and B7 (7.6 g, 10 mmol) were used to replace A2 and B2, and finally product C7 was obtained: 5.9 g, yield: 67%, MS (m / z) (M+): 885.3.

[0069] Synthesis Example 8

[0070]

[0071] Using the same method as in Synthesis Example 2, A8 (4.1 g, 10 mmol) and B8 (6.8 g, 10 mmol) were used to replace A2 and B2, and finally product C8 was obtained: 6.5 g, yield: 74%, MS (m / z) (M+): 887.3.

[0072] Synthesis Example 9

[0073]

[0074] Using the same method as in Synthesis Example 1, A9 (3.4 g, 10 mmol) and B9 (7.6 g, 10 mmol) were used to replace A1 and B1, and finally product C9 was obtained: 5 g, yield: 57%, MS (m / z) (M+): 885.3.

[0075] Synthesis Example 10

[0076]

[0077] Using the same method as in Synthesis Example 2, A2 and B2 were replaced by A10 (3.4 g, 10 mmol) and B10 (7.3 g, 10 mmol), and finally product C10 was obtained: 4.8 g, yield: 56%, MS (m / z) (M+): 859.3.

[0078] Comparative Examples 1-3

[0079] The following provides compounds D1-D3 that were tested during the research process, and their specific structural formulas are as follows:

[0080]

[0081] Material performance evaluation

[0082] In order to further illustrate the technical advantages brought by the present invention, the maximum negative electrostatic potential (ESP) and HOMO energy level of the compounds provided in the embodiments of the present invention are tested and characterized to illustrate that the compounds provided by the present invention have unique advantages:

[0083] 1) Maximum negative electrostatic potential (ESP) of the material: When there are multiple electronegative electron-withdrawing substituents in the material structure, the overall electronegativity of the molecular structure will increase, thereby improving the material's electron transport ability and its ability to coordinate with metal-doped materials, thereby improving the electron injection ability. The electronegativity of a molecule can be evaluated by the maximum negative electrostatic potential (ESP). The larger the absolute value of ESP, the greater the electronegativity of the molecule. ORCA was used to evaluate the ESP of the synthetic example compounds and comparative example compounds under B3LYP / 6-31G** conditions.

[0084] 2) HOMO energy level: The HOMO energy level of the material was tested using cyclic voltammetry. The cyclic voltammetry test used a CS350H electrochemical workstation from Coster Instrument Co., Ltd., with tetrabutyl hexafluorophosphate as the electrolyte dissolved in a dichloromethane solution; the measurement was performed using a three-electrode assembly (working electrode and counter electrode: Pt wire, reference electrode: Pt wire) at room temperature under a nitrogen atmosphere, and ferrocene was used as an internal standard to calibrate the HOMO data to a saturated calomel electrode (SCE). The deeper HOMO energy level of nCGL can effectively reduce the migration of holes to the nCGL layer during the charge separation process, thereby improving the charge separation efficiency.

[0085] The results are shown in Table 1.

[0086] Table 1

[0087] Material No. ESP(eV) HOMO(eV) C1 -2.36 -5.88 C2 -2.32 -5.91 C3 -2.26 -5.82 C4 -2.37 -5.89 C5 -2.25 -5.81 C6 -2.33 -5.92 C7 -2.31 -5.87 C8 -2.35 -5.94 C9 -2.32 -5.89 C10 -2.28 -5.84 D1 -2.03 -5.73 D2 -2.12 -5.81 D3 -2.13 -5.77

[0088] As can be seen from the above data, the ESP absolute value of the compound structure provided by the present invention is relatively large, and the HOMO energy level of the material is significantly deepened, which can significantly improve the electron mobility of the material and the blocking effect on holes. Especially for compounds C1, C4, and C8, by connecting two phosphine substituents on the phenyl group, the ESP absolute value is further increased. On the other hand, for C5, due to the large conjugated structure of anthracene, the phosphine substituents are separated on both sides of the anthracene fragment at the same time, reducing the impact of phosphine on ESP. For compounds C2, C6 and C8, it can be seen that the introduction of nitrogen-containing heteroaryl groups on either side of phenanthroline can deepen the HOMO of the material and enhance its hole blocking ability.

[0089] From the calculation results, it can be seen that by using multiple electronegative groups, the maximum negative electrostatic potential (ESP) and dissociation energy BDE of the entire molecule of compound C1-C10 are significantly better than those of the comparative compounds D1-D3.

[0090] Fabrication and characterization of OLEDs

[0091] Device Embodiment

[0092] The organic electroluminescent device provided by the present invention comprises an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer which are sequentially arranged on a substrate;

[0093] Further, the first hole transport region includes a hole injection layer, a first hole transport layer and a first electron blocking layer; the first electron transport region includes a first hole blocking layer and a first electron transport layer; the charge generation region includes an n-type charge generation layer and a p-type charge generation layer; the second hole transport region includes a second hole transport layer and a second electron blocking layer; the second electron transport region includes a second hole blocking layer, a second electron transport layer and an electron injection layer.

[0094] Furthermore, the light-emitting layer is composed of a main material and a doping material, and the main material of the light-emitting layer can be composed of one molecular material or multiple molecular materials.

[0095] The deuterated organic compound of the present invention can be used in one or more layers of the above-mentioned organic electroluminescent device, preferably used as the n-type charge generation layer material of the device.

[0096] The anode in the embodiment adopts anode materials commonly used in the art, such as ITO, Ag or their multilayer structures. The hole injection layer adopts hole injection materials commonly used in the art, and F4TCNQ, HATCN, NDP-9, etc. are added for doping. The hole transport layer adopts hole transport materials commonly used in the art. The light-emitting layer adopts light-emitting materials and doping materials commonly used in the art, for example, it can be composed of a main material and a doping material. The electron transport layer adopts electron transport materials commonly used in the art. The electron injection layer adopts electron injection materials commonly used in the art, such as LiQ, LiF, Yb, etc. The n-type charge generation layer material adopts the deuterated organic compound provided by the present invention. The cathode adopts materials commonly used in the art, such as metal Al, Ag or metal mixtures (Ag-doped Mg, Ag-doped Ca, etc.).

[0097] The electrode preparation method and the deposition method of each functional layer in this embodiment are conventional methods in the art, such as vacuum thermal evaporation or inkjet printing, etc., which will not be described in detail here. Only some process details and test methods in the preparation process are supplemented as follows:

[0098] Device Example 1

[0099] The substrates used in the present invention were subjected to the following operations: the ITO substrate was patterned so that its luminous area had a size of 3 mm×3 mm, and then water / isopropanol ultrasound, UV / ozone irradiation, and then dried at 100°C. After that, the ITO substrate was mounted on a substrate holder of a vacuum deposition device and the pressure was adjusted so that the vacuum rate became 1×10-7 torr.

[0100] Subsequently, the following operations were performed: first, on the ITO layer (anode) formed on the substrate, a compound HTL-1 and a compound p-dopant-1 (the mass ratio of HTL-1 to p-dopant-1 was 97:3) were vacuum deposited at a thickness of 10 nm to form a hole injection layer; secondly, on the hole injection layer, a compound HTL-1 was vacuum deposited at a thickness of 20 nm to form a first hole transport layer; secondly, on the first hole transport layer, a compound EB-1 was vacuum deposited at a thickness of 5 nm to form a first electron blocking layer; and secondly, on the first electron blocking layer, a mixture of a compound BH-1 and a compound BD-1 was vacuum deposited at a thickness of 20 nm to form a first A light-emitting layer, wherein BH-1 is used as a host and BD-1 is used as a dopant, and the mass ratio of the host to the dopant is 98:2; then, on the above-mentioned first light-emitting layer, a first hole blocking layer is formed by vacuum depositing a compound HB-1 with a thickness of 5 nm; then, on the above-mentioned first hole blocking layer, a first electron transport layer is formed by vacuum depositing a compound ETL-1 and a compound LiQ (the mass ratio of ETL-1 to LiQ is 1:1) with a thickness of 15 nm; then, on the above-mentioned first electron transport layer, a compound C1 and Yb (the mass ratio of C1 to Yb is 98:2) are vacuum deposited with a thickness of 15 nm to form an n-type charge generation layer, and a compound HTL-1 and Compound p-dopant-1 (the mass ratio of HTL-1 to p-dopant-1 is 97:3) is used to form a p-type charge generation layer, and then on the hole generation layer, compound HTL-1 is vacuum deposited with a thickness of 20 nm to form a second hole transport layer, and then on the second hole transport layer, compound EB-1 is vacuum deposited with a thickness of 5 nm to form a second electron blocking layer, and then on the second electron blocking layer, a mixture of compound BH-1 and compound BD-1 is vacuum deposited with a thickness of 20 nm to form a second light-emitting layer, wherein BH-1 is used as a host and BD-1 is used as a dopant, and the mass ratio of the host to the dopant is 98:2; then on the second hole generation layer, compound HTL-1 is vacuum deposited with a thickness of 20 nm to form a second hole transport layer, and then on the second hole transport layer, compound EB-1 is vacuum deposited with a thickness of 5 nm to form a second electron blocking layer, and then on the second electron blocking layer, compound BH-1 is vacuum deposited with a thickness of 20 nm to form a second light-emitting layer. On the second light-emitting layer, the compound HB-1 was vacuum deposited with a thickness of 5 nm to form a second hole blocking layer; then on the above-mentioned second hole blocking layer, the compound ETL-1 and the compound LiQ (the mass ratio of ETL-1 to LiQ is 1:1) were vacuum deposited with a thickness of 15 nm to form a second electron transport layer; then on the above-mentioned second electron transport layer, Yb was deposited with a thickness of 1 nm to form an electron injection layer, and then on the above-mentioned electron injection layer, Mg and Ag (the mass ratio of Mg and Ag is 1:9) were deposited with a thickness of 15 nm to form a cathode, and then on the above-mentioned cathode, the compound CPL-1 was deposited with a thickness of 50 nm to form a covering layer, and a stacked organic electroluminescent device was prepared.

[0101] In addition to the materials used in the present invention, the molecular structures of the remaining materials in each layer of the device are as follows:

[0102]

[0103] Device Examples 2-10

[0104] The above method is used to prepare the compound described in the example into an organic electroluminescent device, wherein C2 to C10 are used to replace C1 to prepare organic electroluminescent device examples 2-10.

[0105] Device Comparison Examples 1-3

[0106] The above method was used to prepare the compounds described in the examples into organic electroluminescent devices, wherein D1 to D3 were used to replace C1 to prepare organic electroluminescent device comparative examples 1-3.

[0107] The OLED devices described above were tested by standard methods. For this purpose, at J = 10 mA / cm 2 The driving voltage, brightness, electroluminescent current efficiency (measured in cd / A) and external quantum efficiency (EQE, measured in percentage) of the organic electroluminescent device are determined at a current density of 200 mA / cm2, which is calculated as a function of the luminous density from the current / voltage / luminous density characteristic line (IVL characteristic line) showing Lambertian emission characteristics. The lifespan LT is defined as the time after which the brightness drops from the initial luminous brightness L0 to a specific proportion L1 when operating at a constant current J; J = 20 mA / cm2 2 The expression L1 = 90% means that at 20 mA / cm 2 When working under LT, the luminance drops to 90% of its initial value L0 after time LT. Similarly, J = 20 mA / cm 2 , L1 = 95% means, at 20mA / cm 2 When working under LT, the luminous brightness drops to 95% of its initial value L0 after time LT.

[0108] The data of various OLED devices are summarized in Table 2. Various parameters of the device examples and the device comparative examples are compared to show the performance data of various OLED devices.

[0109] The test instruments and methods for testing the performance of the OLED devices in the above embodiments and comparative examples are as follows:

[0110] Quantum efficiency CE (cd / A) and color coordinates (CIEy) were tested using a spectrum scanner PhotoResearch PR-735;

[0111] Current density and lighting voltage: tested using a digital source meter Keithley 2400;

[0112] Blue index is obtained by dividing the quantum efficiency CE (cd / A) by the color coordinate (CIEy);

[0113] Life test: Use LT-96ch life test device.

[0114] The performance test results of the above devices are listed in Table 2.

[0115] Table 2 Device performance test results

[0116]

[0117] It can be seen from the device embodiments that the material of the present invention can improve the device efficiency of the material by improving the electron injection ability of the material and reducing the HOMO energy level. Compounds C2, C6, and C8 effectively improve the hole blocking ability by introducing structures such as triazine / pyridine, and have obvious advantages in improving efficiency. For compounds C1 and C4, using a phenyl group to connect the phosphine oxygen substituents together is also helpful for improving efficiency.

[0118] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. An organic compound having multiple heteroatoms, characterized in that: The general structural formula of the organic compound is shown in Formula I: in, Ar1 represents a substituted or unsubstituted aryl group having C6-C60 carbon atoms, a substituted or unsubstituted condensed ring aryl group having C6-C60 carbon atoms, or a substituted or unsubstituted heteroaryl group having C5-C60 carbon atoms; Ar2 represents one of hydrogen, a substituted or unsubstituted aryl group having carbon atoms of C6-C60, and a substituted or unsubstituted heteroaryl group having carbon atoms of C5-C60; Ar3 and Ar4 represent groups represented by formula II; L1 represents a single bond, a substituted or unsubstituted aryl group having carbon atoms of C6-C60, or a substituted or unsubstituted condensed ring aryl group having carbon atoms of C6-C60; L2, L3, and L4 each independently represent a single bond or a phenylene group.

2. The organic compound according to claim 1, characterized in that At least one of Ar1 and Ar2 represents a nitrogen-containing heteroaryl group having C5-C60 carbon atoms.

3. The organic compound according to claim 1, characterized in that Ar1 represents one of phenyl, triazine, naphthyl, anthracenyl, fluorenyl, methyl-substituted fluorenyl, benzimidazole, quinoxaline, quinazoline, and pyridine.

4. The organic compound according to claim 1, characterized in that Ar2 represents one of hydrogen, phenyl, naphthyl, pyridine and pyrimidine.

5. The organic compound according to claim 1, characterized in that The above L1 represents a single bond or a phenylene group.

6. The organic compound according to claim 1, characterized in that The L3 and L4 represent a single bond.

7. The organic compound according to claim 1, characterized in that The organic compound is selected from one of the following general structures: Preferably, the organic compound is selected from Formula I-1, Formula I-2, Formula I-3, Formula I-7, Formula I-8 or Formula I-12, and Ar2 represents pyridine or pyrimidine; Preferably, the organic compound is selected from Formula I-4, Formula I-5, Formula I-6, Formula I-9, Formula I-10, Formula I-11 or Formula I-13, and Ar2 represents one of hydrogen, phenyl, naphthyl, pyridine and pyrimidine.

8. The organic compound according to claim 1, characterized in that The organic compound is selected from one of the following structures:

9. An organic electroluminescent device, characterized in that: It includes an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer, which are sequentially arranged on a substrate; wherein the charge generation region includes one or more organic compounds as described in any one of claims 1 to 8.

10. The organic electroluminescent device according to claim 9, characterized in that: The charge generation region comprises an n-type charge generation layer and a p-type charge generation layer, wherein the n-type charge generation layer comprises one or more organic compounds according to any one of claims 1 to 8.